PERFORMANCE OF TUNA FISH EGGS (Thunnus albacares) IN POST TRANSPORTATION ON THE CLOSE SYSTEM (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
Post-transportation of tuna eggs generally results in hatching rates and larval quality that are not optimal, therefore research is carried out to improve the quality of larvae in rearing. The purpose of this study was to determine the performance of eggs and larvae produced in closed transportation systems. The research was conducted at the Center for Marine Cultivation Research and Fisheries Extension, Gondol-Bali. The treatments in the research activity were the density of tuna eggs, namely 25,000 eggs/L (A), 50,000 eggs/L and 75,000 eggs/L. Data analysis was performed using analysis of variance. Parameters observed in this study were egg hatching rate, prolarvae quality and water quality parameters (Temperature, Salinity, DO, pH and Ammonia). The results showed that each treatment of egg density showed results that were not significantly different (P>0.05). The degree of hatching of tuna eggs after transportation from each treatment showed results that were not significantly different (P>0.05). Treatment with a density of 75,000 eggs/L resulted in the highest average percentage hatching rate of 69.33±3.78%, followed by a density of 25,000 eggs/L of 68.33±3.33% and 50,000 eggs/L of 63.33±3.56%. The development of egg yolk absorption begins on 3rd day and ends on the 5th and 6th day. On day 3rd the larvae begin to need natural food as the energy needed for the survival of the embryo and larvae with a survival activity index of newly hatched larvae of arround 2.29-3.32.